Relationship between maximal jumping height in pole vault and the approach-run velocity evaluated by digitising method or laser method - Kobayashi, F.; Noro, A.; Hatakeyama, S.; Shinohara, Y.; Otsuka, M. (Sports Biomechanics, 2025)
The first objective was to validate various approach-run velocities obtained using body-only method (digitising only the athlete`s body) or laser method (using a laser displacement metre) against the whole-system method (digitising both the athlete`s body and pole) during pole vaulting. The second objective of this study was to clarify the relationship between the approach-run velocity obtained by different three methods and the maximal height of the athlete`s centre of mass (COM) during the clearance. Eighteen male athletes performed 96 pole-vaulting attempts in outdoor competitions. Bland—Altman plots indicated that only the peak approach-run velocity obtained by the body-only method had negligible bias, while other parameters obtained by body-only digitising and laser methods contained several errors. Since such bias could cause problems, using conventional digitising and laser methods requires careful handling. The association between maximal COM height during the clearance and peak approach-run velocity was extremely large for all three methods. In contrast, although the relationship between the maximal COM height and the decrease in approach-run velocity was large for both digitising methods, it was weakened for laser method. Consequently, based on the approach-run velocity parameters, different calculation methods for approach-run velocity parameters resulted in varying relationships with jumping performance.